ANALISIS ATAS PELABELAN HALAL DSN-MUI TERHADAP SAHAM PERUSAHAAN TAMBANG BATU BARA DALAM PERSPEKTIF FIKIH LINGKUNGAN - Fathoni, Sulthon (Yurisprudentia: Jurnal Hukum Ekonomi, 2023)
This study analyzes the Sharia shares of coal mining companies from the perspective of Environmental Jurisprudence. Several shares of coal mining companies have obtained the Sharia label from the DSN-MUI. This raises questions when compared to the reference of environmental activists who state that coal is a bad energy and there is an attempt to classify it as energy that must be abandoned because it damages the environment. In addition, environmental fiqh has developed rapidly. Even the MUI has issued a fatwa on environmentally friendly mining. This research method is descriptive analysis using Environmental Jurisprudence Analysis knife. The principles developed in Environmental Jurisprudence will be presented and used to analyze the process of sharing coal mining shares and see the environmental concept of coal that is currently developing. Especially those popularized by environmental activists. This research results that the Islamic process does not see coal as harmful to the environment. Besides that, the process is only carried out in a normative Fiqh manner without looking at the issues that develop in the field about the number of mining companies that damage the environment or the issue that coal is an energy that is not environmentally friendly.